Impact of Gall-Forming Insects on Global BVOC Emissions and Climate: A Perspective - Noe, Steffen M.; Niinemets, Ülo (Frontiers in Forests and Global Change, 2020)
Processes that change the carbon exchange between terrestrial ecosystems and the atmosphere are pivotal in understanding climate impact on global scale. Volatile organic compounds (VOC) emissions change substantially with biotic stressors like gall-forming insects. We provide a first global estimate of the effect of changes in VOC emission dynamics due to parasitic gall-forming insects on broad-leaved tree species. Overall, the effect investigated lead to a reduction in VOC emissions on global scale which lead to changes in the carbon driven climate feedback loop.